In situ synthesized SnO2 nanorod/reduced graphene oxide low-dimensional structure for enhanced lithium storage. (31st January 2018) - Zhang, Wei; Xiao, Xuezhang; Zhang, Yiwen; Li, Junpeng; Zhong, Jiayi; Li, Meng; Fan, Xiulin; Wang, Chuntao; Chen, Lixin
Abstract: A unique SnO2 nanorod (NR)/reduced graphene oxide (RGO) composite morphology has been synthesized using the in situ hydrothermal method, for use as an anode material in lithium-ion batteries. The SnO2 NR adhering to the RGO exhibits a length of 250–400 nm and a diameter of 60–80 nm without any obvious aggregation. The initial discharge/charge capacities of the SnO2 NR/RGO composite are 1761.3 mAh g −1 and 1233.1 mAh g −1, with a coulombic efficiency (CE) of 70% under a current density of 200 mA g −1, and a final capacity of 1101 mAh g −1 after 50 cycles. The rate capability of the SnO2 NR/RGO is also improved compared to that of bare SnO2 NR. The superior electrochemical performance is ascribed to the special morphology of the SnO2 NRs—which plays a role in shorting the transmission path—and the sheet-like 2D graphene, which prevents the agglomeration of SnO2 and enhances conductivity during the electrochemical reaction of SnO2 NR/RGO.